Education Workforce Well-being: Policy, Change and Leadership - Corbett, Stephen (Emerald Publishing Limited, 2024)
Corbett widens the discussion on well-being in the education workforce, drawing not only on education but also human resource management and leadership research and providing a critical analysis that highlights not only the challenges but research-informed recommendations for managers, leaders and policy makers working in education.